A note on Hausa plurals - Donald A. Burquest (LibraryPress@UF, 1989)
In their presentation of three-dimensional phonology, Halle and Vergnaud [1980, 1981] propose that Hausa singular nouns are morphologically complex like the plural forms, composed of a stem plus a singular suffix. This paper argues that this analysis is incorrect, but that the proposal that singular nouns are morphologically complex is not necessary to demonstrate the usefulness of an autosegmental analysis. Among the arguments presented is a claim that palatalization of coronal obstruents in Hausa is a cyclic rule, but one applying only to derived words, not stems. It is further demonstrated that Hausa makes use of rules which in parallel fashion delete syllable nuclei occurring directly preceding syllable nuclei, and syllable appendices occurring directly preceding syllable appendices. Thus, the two approaches of autosegmental phonology and lexical phonology work together to account for the facts of the Hausa nominal forms in question.